2021
DOI: 10.3390/ijerph18189522
|View full text |Cite
|
Sign up to set email alerts
|

Translation of the Weight-Related Behaviours Questionnaire into a Short-Form Psychosocial Assessment Tool for the Detection of Women at Risk of Excessive Gestational Weight Gain

Abstract: The identification and measurement of psychosocial factors that are specific to pregnancy and relevant to gestational weight gain is a challenging task. Given the general lack of availability of pregnancy-specific psychosocial assessment instruments, the aim of this study was to develop a short-form psychosocial assessment tool for the detection of women at risk of excessive gestational weight gain with research and clinical practice applications. A staged scale reduction analysis of the weight-related behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Additionally, contrary to our hypothesis, we found that young women with higher levels of DE thoughts had more positive attitudes toward gestational weight gain. This is unexpected as we expected that women with significant preoccupations with food and eating would be less accepting of weight gain, even during pregnancy [ 24 ]. A possible explanation for this could be that young women who are preoccupied with their weight, body shape, and eating habits would not feel as pressured to avoid gaining weight if they were to become pregnant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, contrary to our hypothesis, we found that young women with higher levels of DE thoughts had more positive attitudes toward gestational weight gain. This is unexpected as we expected that women with significant preoccupations with food and eating would be less accepting of weight gain, even during pregnancy [ 24 ]. A possible explanation for this could be that young women who are preoccupied with their weight, body shape, and eating habits would not feel as pressured to avoid gaining weight if they were to become pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…The Weight-Related Behaviors Questionnaire (WRB-Q) is a validated measure used to assess pregnancy-related factors that affect weight gain and retention during and after pregnancy [ 27 ]. The original measure contains 49 items, however we used the short-form 12 item questionnaire called the Gestational Weight Gain Psychosocial Risk Assessment Tool to look for women that are at risk for gaining excessive weight during pregnancy [ 24 ]. The adapted questionnaire was split into three subscales: Self-Efficacy, Attitudes Toward Weight Gain, and Body Image.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation